Steps in Conducting a Photovoice Project - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
The infograph shows how Photovoice can be used in upscaling climate-smart agriculture practices. It provides the step-by-step process in conducting a Photovoice project